Reflection of Multiple Loading in The Deformation Model for Reconstructed Reinforced Concrete - V. G. Murashkin (Железобетонные конструкции)
During the reconstruction, or upon expiration of the service life, as well as after external impact, reinforced concrete structures require examination and verification calculations. Existing diagrams of concrete deformation are focused on designing new structures and are not adapted to the concretes of the reconstructed structures.Using the exponential model of concrete deformation makes it possible to describe the resistance of concrete during reconstruction, including after repeated cyclic loading.A technique for creating an individual deformations model under cyclic load during the reconstruction is demonstrated on a specific example.